New perspectives on community-acquired pneumonia in 388 406 patients. Results from a nationwide mandatory performance measurement programme in healthcare quality. Issue 12 (18th May 2009) - Ewig, S; Birkner, N; Strauss, R; Schaefer, E; Pauletzki, J; Bischoff, H; Schraeder, P; Welte, T; Hoeffken, G
Abstract : Background: The database of the German programme for quality in healthcare including data of every hospitalised patient with community-acquired pneumonia (CAP) during a 2-year period (n = 388 406 patients in 2005 and 2006) was analysed. Methods: End points of the analysis were: (1) incidence; (2) outcome; (3) performance of the CRB-65 (C, mental confusion; R, respiratory rate ⩾30/min; B, systolic blood pressure <90 mm Hg or diastolic blood pressure ⩽60 mm Hg; 65, age ⩾65 years) score in predicting death; and (4) lack of ventilatory support as a possible indicator of treatment restrictions. The CRB-65 score was calculated, resulting in three risk classes (RCs). Results: The incidence of hospitalised CAP was 2.75 and 2.96 per 1000 inhabitants/year in 2005 and 2006, respectively, higher for males (3.21 vs 2.52), and strongly age related, with an incidence of 7.65 per 1000 inhabitants/year in patients aged ⩾60 years over 2 years. Mortality (13.72% and 14.44%) was higher than reported in previous studies. The CRB-65 RCs accurately predicted death in a three-class pattern (mortality 2.40% in CRB-65 RC 1, 13.43% in CRB-65 RC 2 and 34.39% in CRB-65 RC 3). The first days after admission were consistently associated with the highest risk of death throughout all risk classes. Only a minority of patients who died had received mechanical ventilation during hospitalisation (15.74%). Conclusions: Hospitalised CAP basically is a condition of the elderly associated with a higher mortality than previously reported. It bears a considerable risk of early mortality, even in low risk patients. CRB-65 is a simple and powerful tool for the assessment of CAP severity. Hospitalised CAP is a frequent terminal event in chronic debilitated patients, and a limitation of treatment escalation is frequently applied.